2011
DOI: 10.1142/s1088424611004312
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrochemical and photochemical investigation of the water-soluble tin(IV) tetrakis(2-N-hydroxyethyl-4-pyridinium)porphyrin photocatalyst

Abstract: The water-soluble tin(IV) tetrakis(2-N-hydroxyethyl-4-pyridinium)porphyrin 1 photocatalyst was synthesized in good yield and its structure determined by single crystal X-ray crystallography. Electrochemical measurements on tin(IV) porphyrin 1 reveal a range of complex redox processes that are highly dependent on the pH and electrode used. The cathodic processes at ca. -0.6 to -0.8 V were assigned to electrochemical processes on the pyridyl moiety following differential pulse voltammetry and spectroelectrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These spectral features were previously attributed to π-radical anion and/or phlorin by different authors or overlapping of the spectral features of these species. 20,41,45,[51][52][53][54]84,89,113,114 Moreover, both π-radical anion and phlorin are easily oxidized by oxygenation, resulting in the disappearance of their spectral features. Therefore, currently, we have no reliable data to attribute these spectral features specifically either to π-radical anion or phlorin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These spectral features were previously attributed to π-radical anion and/or phlorin by different authors or overlapping of the spectral features of these species. 20,41,45,[51][52][53][54]84,89,113,114 Moreover, both π-radical anion and phlorin are easily oxidized by oxygenation, resulting in the disappearance of their spectral features. Therefore, currently, we have no reliable data to attribute these spectral features specifically either to π-radical anion or phlorin.…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to detect oxidation potentials for the latter porphyrins since they are oxidized at higher potentials, which is in agreement with ref . Additionally, possible impurities in the porphyrin samples and dimerization of pyridinium groups (SnTMPyP) might be responsible for some features on complex CVs of Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalysis of the Pt 2+ and Au + reduction leads to form of nanostructures. [105,106] The mechanism of the photocatalytic reactions of the main group porphyrin/phthalocyanine complexes remains the actual task; using photocatalytic experiment on tin(IV) porphyrin under anaerobic conditions with triethanolamine as a sacrifical donor, the authors [107] have shown that tin(IV) porphyrin π-radical anion is perhaps not the species responsible for the apparent ability tin(IV) porphyrins to photocatalytically reduce substrates.…”
Section: The Main Group Porphyrin/phthalocyanine Complexes As Catalystsmentioning
confidence: 99%
“…There are a number of common structural and topological features that have been observed in architectures containing TPyP which are dictated by its rigidity and self-complementarity. These features include a variety of one-dimensional chains, , two-dimensional nets based on the (4, 4) topology ,, which can be cross-linked into three-dimensional networks, and three-dimensional architectures including the NbO, , CdSO 4 , , PtS, face-centered cubic, and α-polonium nets . Further, the architectures that have been encountered include a large number of potentially porous networks, often containing disordered solvent molecules. The range of architectures expands when TPyP is combined with noncovalently bound coformers.…”
Section: Introductionmentioning
confidence: 99%